Illocutionary Acts in Main Character’s Dialogue of “Maleficent: Mistress of Evil” Movie - Wijayanti, Kurnia Sari; Yulianti, Fitri (Journal of English Teaching and Learning Issues, 2020)
The aims of the article are to find out: 1) kinds of illocutionary acts which are produced by the main characters in “Maleficent: Mistress of Evil” movie, and 2) the most dominant illocutionary acts.  In analyzing the data, the authors used descriptive qualitative method.  The object of this study was main character’s dialogue of “Maleficent: Mistress of Evil” movie.  The authors did these following steps: watched the movie, found the transcript, identified the dialogues of main character, classified them using Searle’s theory, and interpreted the meaning of utterances.  Here are 52 utterances with illocutionary acts. The results were: 1) Representative (assertive) (65%), 2) Directive (19%), 3) Expressive (8%), 4) Commissive (6%), and 5) Declarative (2%) in scale of 100%. Representative (assertive) was the most dominant. This study can be a reference for learning pragmatics, especially illocutionary acts. The teachers can also use movie as speech acts teaching media.